METODE KUADRAT TERKECIL BERBOBOT DAN APLIKASINYA PADA MODEL MATEMATIKA KONSUMSI BENSIN - Riris Siagian; Imran M.; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the application of the least squares and weighted least squares method to determine the amount of fuel consumption at a given distance in the use of vehicles in and out of town at the same time using mathematical models. This articleis a review of Izzo’s article [Mathematics Magazine 73(3):226-231]. Computational examples using real data show that the solution given by the weighted least squares method to a mathematical model of gasoline consumption more in line with the real situation.